A Critical Review and Evaluation of the Textbook Entitled Designing the Digital Library Based on the Standards and Criteria of University Textbooks - Zeinab Papi (International Journal of Digital Content Management, 2023)
Objective: The purpose of this study was analytical review of the book Designing the Digital Library, written by Mehdi Alipoor-Hafezi and published by SAMT in 2019 based on the criteria and standards of the university textbooks. The type of research was applied in terms of  purpose. As regarded method, it was a mixed-method approach. The analysis, review  and extraction of required data have been simultaneous. The checklist was used for assessing formal writing structure and content features on a Likert-type 5-pointed scale. Author's expertise in the field can be mentioned as the main advantage of the book. The textbook is the only work in Persian in the field of designing digital libraries. A separate chapter on legal  issues in digital libraries can also be considered as another positive point of this work. At the same time, this work has also notable points for improvement, the most important of which are   writing points. In general, the work in hand in terms of evaluation of formal writing structure and content criteria received scores of 46, 46, 63 and 63, respectively and achieved at least 70 percentage points, passing as a  book appealing to its audience. In spite of some defects and weaknesses, the studied textbook is one of few books on designing digital libraries and suitable for students and audience.